Computational study on single molecular spectroscopy of tyrosin-glycine, tryptophane-glycine and glycine-tryptophane. Issue 1 (December 2017) - Yang, Bing; Liu, Shixue; Lin, Zijing
Abstract Quantum chemistry calculations play a fundamental role in revealing the molecular structures observed in gas-phase spectroscopic measurements. The supersonic jet cooling widely used in single molecular spectroscopy experiment is a non-equilibrium process and often causes confusion on the theoretical and experimental comparison. A computational approach is proposed here to account for the effect of the non-equilibrium cooling on the experimental spectra and applied to the cases of tyrosin-glycine (YG), tryptophane-glycine (WG) and glycine-tryptophane (GW). The low energy conformers of YG, WG and GW are obtained through thorough conformational searches. The structural features and equilibrium distributions of conformations and the energy barriers for conformer conversions are then determined. Three classes of transition energy barriers, high, medium and low, are found for the conversions among conformers with distinctly different, similar and the same structural types, respectively. The final conformation populations are determined by assuming an initial temperature of about 450 K and allowing for only the conformation conversion with a low energy barrier to occur during the rapid cooling process. The results provide a natural explanation for the numbers of YG, WG and GW conformations observed experimentally. The theoretical conformation assignments are also in good agreement with the experimental IR data.